DNA metabarcoding of benthic algae and associated eukaryotes from Lake Baikal in the face of rapid environmental changes - Yu. S. Bukin; L. S. Kravtsova; T. E. Peretolchina; A. P. Fedotov; A. E. Tupikin; M. R. Kabilov; D. Yu. Sherbakov; E. V. Mincheva (Вавиловский журнал генетики и селекции)
Here we report new data describing the biodiversity of phytobenthic communities based on DNA-metabarcoding using the 18S rDNA marker and the Illumina MiSeq system. The study was initiated due to the blooming of filamentous algae (mainly of the genus Spirogyra) and cyanobacteria in the coastal zone of Lake Baikal under climate change and anthropogenic impact. The composition and taxonomic diversity of algae and other organisms associated with them on different sites of Lake Baikal (near Bolshoi Ushkaniy Island, in Listvennichny Bay) and in the Kaya (within the city of Irkutsk, located in the same drainage basin as Lake Baikal) were determined using DNAmetabarcoding. About 15 thousand reads of the 18S rRNA marker were obtained by applying NGS (next-generation sequencing). The species of algae dominating in the number of reads, as well as the difficult-to-identify taxa (Stramenopiles, Alveolata, Euglenozoa, Chromista, Rhizaria, Amoebozoa, etc.), which play an important role in the functioning and formation of the structure of algal communities, were revealed. The Shannon index of the communities studied ranges from 1.56 to 2.72. The advantages and weaknesses of using DNA-metabarcoding based on the 18S rRNA gene fragment for studying the structure of algal communities are shown. The advantage of this method is the possibility to more fully determine the diversity of eukaryotes taxa, which are difficult to identify by morphology, without involving a large number of specialists, while the disadvantage of the method is the distortion that may occur during the PCR. Here, ways of solving this problem are proposed. The results of the study show that the analysis of the minor component of the eukaryotic community in samples (organisms with low biomass) consisting of a mixture of multicellular and unicellular organisms requires a read-depths of at least 100,000 sequences per sample. In general, the DNA-metabarcoding method is recommended for studying the structure of algal communities and eukaryotes associated with them.